In vitro antioxidant activity of Cayratia mollissima - an endangered species of Western Ghats of India - Jammanakatti, Savitha V; J, Prashanth S; A, Ashwini; Nayak, Shruthi; Shettar, Arun K; V, Sowmya (Journal of Postharvest Technology, 2022)
India's tropic climate is versatile to grow colorful Vegetables and Fruits. The colourful fruits and vegetables are loaded with Vitamins, minerals,  and Phytochemicals. Amongst the Various Fruits and Vegetables, one of the rarest and endangered fruit is Cayratia mollissima, which is used  by a community of people called Havyaka Brahmins on a special occasion called Aati Amavasya. Using DPPH and Ferric reducing power as  an antioxidant model, the antioxidant potential of aqueous and ethanol extracts of Cayratia mollissima fruit were found out to explore its health  benefits. The findings from this In vitro study revealed that Cayratia mollissima fruit extracts could serve as Oxygen radical inhibitors.  Evaluation of TAC-Total Anti-oxidant Capacity of the extracts were done using FRAP and DPPH assay method. To measure a drug’s potency,  the Half-maximal inhibitory concentration (IC50) is broadly used. The TAC of aqueous extract and ethanol extract through the FRAP assay  method is IC50=354.25 µg and IC50=189.56 µg respectively. The TAC of aqueous extract and ethanol extract through the DPPH assay method  is IC50=184.94 µg and IC50=163.88 µg respectively.
Keywords: Cayratia mollissima; Ethanol extract,; aqueous extract; , DPPH assay,; FRAP assay